Research progress on physical and chemical properties of coal gasification slag and its preparation of building materials - Xiaowei GU; Xiaowei GE; Shaoqian LIU; Xuecheng DING; Li WANG; Dongwei HUANG; Dawei WANG; Yile MA (Meitan kexue jishu)
With the rapid development of the modern coal chemical industry, coal gasification technology plays an increasingly important role in the clean and efficient utilization of energy. The discharge of coal gasification slag (CGS), an industrial by-product of the gasification process, continues to increase. However, the comprehensive utilization rate of CGS remains low, with most of the material disposed of through landfilling or stockpiling, which not only occupies land resources but also causes a series of ecological and environmental problems, such as heavy metal leaching and alkaline pollution. These issues seriously restrict the green, low-carbon transformation and sustainable development of the coal chemical industry. In recent years, the resource attributes of CGS have gained growing attention under the dual-carbon strategy. Its potential pozzolanic activity, abundant residual carbon content, high specific surface area, and partially glassy phase structure endow it with considerable application potential. Domestic and international studies indicate that, through appropriate activation strategies and mix design optimization, CGS can partially or completely replace cement, serving as a concrete admixture, cementitious material, or brick-making raw material, thereby enabling its resource utilization in the construction material sector. Nevertheless, the current utilization of CGS is limited by fragmented application routes, unclear reaction mechanisms, and an underdeveloped theoretical framework, which hinder its further promotion and application. The formation mechanism and classification of CGS are systematically reviewed, categorizing it into coal gasification coarse slag (CGCS) and coal gasification fine slag (CGFS). A comparative analysis of CGCS and CGFS in terms of chemical composition, mineral phases, microstructure, particle size distribution, and specific surface area reveals differences in their fundamental properties and resource utilization potential, while also assessing environmental impact risks. Typical application models in the field of construction materials are summarized, including CGS use in low-carbon cementitious binders, concrete admixtures, building wall materials, and green recycled aggregates. These applications demonstrate CGS potential in green and sustainable construction. The technical bottlenecks in activity excitation, residual carbon removal, interface compatibility and long-term durability are analyzed. The applicability of CGS in different utilization scenarios is further clarified; for instance, CGCS, with its lower carbon content, is more suitable for cementitious or brick materials. In addition, combined with the current research hotspots and policy orientation, the future development direction of CGS resource utilization is prospected. It is proposed to promote the development of CGS in the direction of high performance, low carbonization and engineering by means of multi-source collaborative excitation, all-solid waste coupling utilization, functional material preparation, performance regulation mechanism construction and life cycle assessment.